Pengaruh kesadaran merek, sikap dan nilai yang dirasa terhadap niat pembelian ulang Sarimi di Surabaya Timur - Adhe Bagus Tirta Kusuma; Laila Saleh Marta' (STIE Perbanas Surabaya, 2015)
Brand awareness is one of the factors which can make the consumers identify, under-stand and recognize a specific brand and finally can lead them to have a repurchase in-tention towards the products. Besides that, the reaction of consumer‟s sense about the product also affects consumer‟s decision to purchase the product. A consumer decisions to purchase may also be affected by the perceived value or benefits of the product, and then finally consideration to purchase the product. This study attempts to analyze the relevance of brand awareness, attitude, and perceived value of the product repurchase intention. This research took the sample of 100 consumers of instant noodles with its trade mark of Sarimi in East Surabaya. The results shows that brand awareness, atti-tude, and perceived value both partially and simultaneously affect repurchase intention of the instant noodle with Sarimi trade mark in East Surabaya.